Combating fake news in Malaysia – An analysis of anti-fake news act 2018 (AFNA) - Asril Amirul, Zakairah; Nazli Ismail, Nawang; Aminuddin, Mustaffa (2018)
The phenomenon development of the Internet and various types of social networking services such as WhatsApp, Telegram, Twitter, Facebook and many others has greatly facilitated the communication of news and information in this era. Unfortunately, these web based communication platforms have been manipulated by certain people to disseminate fake news in the society. The mass circulation of such news in the cyber world has not only confused the people, but also threatened the safety, economy and well-being of the Malaysian citizens and the country itself. In combating this startling issue, the Malaysian Parliament has on 2 April 2018 passed the Anti-Fake News Act 2018 (AFNA), which came into force on 11 April 2018. Nonetheless, a critical issue arose as to whether AFNA would have the effect of depriving the people’s fundamental right to freedom of speech and expression which is explicitly guaranteed by Article 10 of the Federal Constitution. As such, this paper aims to scrutinise the provisions of AFNA in details and its impacts on the people in the country. Comparative analysis will also be made with other countries that have introduced anti-fake news law in order to examine the suitability and efficacy of AFNA.